2017
DOI: 10.3389/fimmu.2017.01166
|View full text |Cite
|
Sign up to set email alerts
|

Human Gut Symbiont Roseburia hominis Promotes and Regulates Innate Immunity

Abstract: ObjectiveRoseburia hominis is a flagellated gut anaerobic bacterium belonging to the Lachnospiraceae family within the Firmicutes phylum. A significant decrease of R. hominis colonization in the gut of ulcerative colitis patients has recently been demonstrated. In this work, we have investigated the mechanisms of R. hominis–host cross talk using both murine and in vitro models.DesignThe complete genome sequence of R. hominis A2-183 was determined. C3H/HeN germ-free mice were mono-colonized with R. hominis, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
108
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 44 publications
5
108
1
Order By: Relevance
“…Our data revealed a positive correlation between four Lachnospiraceae‐related OTUs and occludin expression, and supplementation with R. hominis prevented the decreases in occludin mRNA and protein expression, accompanied by an increase in butyrate production in the intestinal contents. This is consistent with the finding that R. hominis colonization of germ‐free mice can affect intestinal barrier function genes . These results suggest the potential role of specific butyrate‐producing bacteria in preventing gut leakage through their metabolites.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data revealed a positive correlation between four Lachnospiraceae‐related OTUs and occludin expression, and supplementation with R. hominis prevented the decreases in occludin mRNA and protein expression, accompanied by an increase in butyrate production in the intestinal contents. This is consistent with the finding that R. hominis colonization of germ‐free mice can affect intestinal barrier function genes . These results suggest the potential role of specific butyrate‐producing bacteria in preventing gut leakage through their metabolites.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the finding that R. hominis colonization of germ-free mice can affect intestinal barrier function genes. 39 These results suggest the potential role of specific butyrate-producing bacteria in preventing gut leakage through their metabolites. Moreover, it is reported that butyrate could induce MUC2 mRNA expression and MUC2 secretion in goblet-like cell, 40 as well as promote the assembly of occludin dependent on AMPK pathway.…”
Section: Discussionmentioning
confidence: 91%
“…Consistently with our findings, these genera were depleted in 16S microbiota profiles of individuals suffering from post-transplantation [35] and nosocomial diarrhoea, including Clostridium difficile infection [36]. Moreover, Roseburia and Ruminococcus species have been shown to prevent gut inflammation by strengthening gut barrier function in mice [37] and by enhancing starch fermentation in humans [38], respectively. Subjects who did not experience diarrhoea during the travel had a richer and more diverse microbiota after travel than before.…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported that the abundance of Roseburia genus was less in several diseases (ulcerative colitis, type 2 diabetes, and neuronal diseases), and that this bacterium could serve as probiotics for restoration of beneficial flora. (22) Patterson et al (23) have demonstrated that mono-association of mice with Roseburia hominis bacteria results in specific bidirectional gene expression patterns. A set of genes thought to be important for host colonization are induced in Roseburia hominis, while the host cells respond by strengthening the gut barrier func-tion and enhancing regulatory T cell population expansion, possibly via TLR5-flagellin signaling.…”
Section: Discussionmentioning
confidence: 99%